The Influence of Labor Discipline, Compensation, and Work Environment on the Performance of Employees of the Manpower and Transmigration Office of Yogyakarta City - Chalil, Nurlita Rafiqah; Subarjo, Subarjo (Research Horizon, 2024)
This research aims to analyze the influence of Work Discipline, Compensation and Work Environment on employee performance at the Yogyakarta City Manpower and Transmigration Service. The sample in this study was 80 respondents who were employees of the Yogyakarta City Manpower and Transmigration Service. The data collection technique used was a survey method with the research instrument used was a questionnaire. The instrument test results stated that the data in this study were valid and reliable. The classical assumption test states that the data in this study is normally distributed and produces a regression model that is free from multicollinearity and heteroscedasticity. The results of this research prove that Work Discipline, Compensation and Work Environment simultaneously and significantly influence employee performance at the Yogyakarta City Manpower and Transmigration Service. This can be proven by the significance level obtained from this research, namely Adjusted R-square of 0.516. It can be interpreted that the contribution of Work Discipline, Compensation and Work Environment is 51.6%. Meanwhile, the rest is influenced by other variables that are not included in this research model